OPTIMIZATION OF CIJANGGEL DRINKING WATER DISTRIBUTION NETWORK IN NGAMPRAH AND CISARUA SUBDISTRICT, BANDUNG BARAT DISTRICT - Maranatha Gloriani, Dameria
PT. PMGS is a Regionally Owned Enterprise (BUMD) that serves the community's clean water needs. PT. PMGS has several SPAM to serve customers, one of which is Cijanggel SPAM. Cijanggel SPAM serves Ngamprah Subdistrict and Cisarua Subdistrict using gravity drainage methods. Cijanggel SPAM uses water sources from the Cijanggel River. Cijanggel River has a river flowrate of 50 liters / second. From the river, water is transmitted to the reservoir before being distributed to customers. The flow of distribution water from the reservoir to the customer's house is 43 liters / second. However, based on calculations, it was found that the water sold or reached the customer was only 23 liters / second. This is a problem because the NRW (Non Revenue Water) value in the Cijanggel SPAM distribution network reaches 43%. This far exceeds the National PDAM NRW tolerance standard of 20% (Minister of Public Works Regulation no. 20 / PRT / M / 2006). Therefore, a method is needed to reduce NRW to reach the national standard. There is an efficient District Meter Area (DMA) method in dealing with NRW. Three alternatives aimed at suppressing NRW values were designed to overcome these problems in the study area. The three alternatives are designed to use DMA with differences based on the amount of SR in the DMA zone, the number of meters of water to measure inlet and outlet water, contour variations, and the need for additional pipes. The alternative chosen is the alternative that best meets the most design criteria and the minimum pipe addition requirements. Based on these considerations, the alternative chosen is alternative 3 with one DMA zone and still maintaining the two existing branches.